Predictors of Progression in Intraplaque Hemorrhage Volume in Patients With Carotid Atherosclerosis: A Serial Magnetic Resonance Imaging Study - Mingming, Lu; Peng, Peng; Lichen, Zhang; Shaohua, Liu; Fei, Yuan; Hongtao, Zhang; Shitong, Liu; Yao, He; Xihai, Zhao; Jianming, Cai (Frontiers in Neurology, 2022)
Background and purpose： This study aimed to investigate the arterial disease risk factors for the progression of intraplaque hemorrhage (IPH) in patients with carotid atherosclerosis using serial high resolution magnetic resonance (MR) imaging. Methods： Consecutive symptomatic patients who had MRI evidence of intraplaque hemorrhage present in the ipsilateral carotid artery with respect to the side of the brain affected by stroke or TIA were recruited in the study. All the patients underwent follow-up MR imaging more than 6 months after baseline. Baseline information and carotid plaque features of patients were collected. The annual change of IPH and other carotid plaque morphology was calculated. Logistic regression and receiver-operating-characteristics (ROC) curve were conducted to evaluate the risk factors for the progression of IPH. Results: Thirty-four symptomatic patients (mean age: 67.1 years, standard deviation [SD]: 9.8 years, 27 males) were eligible for the final analysis and contralateral plaques containing IPH were seen in 29 of these patients (making 45 plaques with IPH in total). During mean 16.6 months (SD: 11.0 months) follow-up, the overall annual change of IPH volume in 45 plaques with IPH was mean -10.9 mm3 (SD: 49.1 mm3). The annual progression of IPH was significantly associated with taking an antiplatelet agent at baseline (OR: 9.76; 95%CI: 1.05 to 90.56; p=0.045), a baseline history of current or past smoking (OR: 9.28; 95%CI: 1.26 to 68.31; p=0.029), and larger baseline carotid plaque volume (OR: 1.36 per 10 mm3; 95%CI: 1.02 to 1.81; p=0.032) after adjustments for confounding factors. ROC analysis indicated that the combination of these three risk factors in the final model produced good discriminatory value for IPH progression (area-under-the-curve: 0.887). Conclusions: Taking an antiplatelet agent at baseline, a baseline history of current or past smoking, and larger baseline plaque volume were independently associated with the progression of IPH volume. Our findings indicate that awareness and management of such risk factors may reduce the risk of intraplaque hemorrhage progression and, therefore, may reduce the risk of arterial disease complications, including stroke.